1990
DOI: 10.1007/bf01580858
|View full text |Cite
|
Sign up to set email alerts
|

Chvátal closures for mixed integer programming problems

Abstract: Chvatal introduced the idea of viewing cutting planes as a system for proving that every integral solution of a given set of linear inequalities satisfies another given linear inequality. This viewpoint has proven to be very useful in many studies of combinatorial and integer programming problems. The basic ingredient in these cutting-plane proofs is that for a polyhedron P and integral ve.:tor w, if max( wx Ix E P, wx integer}= I, then wx"' t is valid for all integral vectors in P. We consider the variant of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
254
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(255 citation statements)
references
References 20 publications
1
254
0
Order By: Relevance
“…Split cuts [12], Gomory Mixed Integer (GMI) cuts [17], and Mixed Integer Rounding (MIR) cuts [23,24] are some of the most effective valid inequalities for Mixed Integer Linear Programming (MILP) [8]. While they are known to be equivalent [15,24], each of them provide different advantages and insights.…”
Section: Introductionmentioning
confidence: 99%
“…Split cuts [12], Gomory Mixed Integer (GMI) cuts [17], and Mixed Integer Rounding (MIR) cuts [23,24] are some of the most effective valid inequalities for Mixed Integer Linear Programming (MILP) [8]. While they are known to be equivalent [15,24], each of them provide different advantages and insights.…”
Section: Introductionmentioning
confidence: 99%
“…One example of intersection cuts is the split cut [16]. A split cut is derived from the split set described in Proposition 2.1 by using (3).…”
Section: Convex Hull Of (2) Via Intersection Cutsmentioning
confidence: 99%
“…This is because such instances can be decomposed row-wise and solved independently. Since each row has only one integer variable, the split closure is the convex hull; see [16].…”
Section: Density and Multi-row Experimentsmentioning
confidence: 99%
“…Split cuts are obtained from disjunctions that are more general than the simple variable disjunctions, namely α x 1 ≤ β or α x 1 ≥ β +1, where (α, β) ∈ Z n 1 +1 and x 1 is the vector of integer variables. Despite the generality of the split disjunction, Cook et al (1990) provide an example to show that the split rank of a MILP-G could be infinite. Furthermore, the separation of split cuts is shown to be N P-hard (Caprara and Letchford, 2003).…”
Section: Connections With the Literature And Conclusionmentioning
confidence: 99%
“…This characterization is a generalization of the sequential convexification process of Balas (1979) for MILP with binary variables (MILP-B). However, it is important to note that the same sequential process of convexification (one variable at a time) does not yield the convex hull of MILP-G in finitely many steps (Owen and Mehrotra, 2001 Cook et al (1990) showed non-convergence for MILP-G using split disjunctions, and even in the case of MILP-B, Sen and Sherali (1985) presented examples of non-convergence in which facet inequalities of two-term (simple) disjunctions are derived to cut away the solution to the most recent LP relaxation. Chen et al (2009) use the CPT algorithm to solve the above instances in finitely many iterations.…”
Section: Introductionmentioning
confidence: 99%